Macroalgal responses to ocean acidification depend on nutrient and light levels - Celis-Plá, Paula S. M.; Hall-Spencer, Jason M.; Horta, Paulo Antunes; Milazzo, Marco; Korbee, Nathalie; Cornwall, Christopher E.; Figueroa, Félix L. (Frontiers in Marine Science, 2015)
Ocean acidification may benefit algae that are able to capitalise on increased carbon availability for photosynthesis but is expected to have adverse effects on calcified algae through dissolution. Shifts in dominance between primary producers will have knock-on effects on marine ecosystems and will likely vary regionally, depending on factors such as irradiance (light vs shade) and nutrient levels (oligotrophic vs eutrophic). Thus experiments are needed to evaluate interactive effects of combined stressors in the field. In this study, we investigated the physiological responses of macroalgae near a CO2 seep in oligotrophic waters off Vulcano (Italy). The algae were incubated in situ at 0.2 m depth using a combination of three mean CO2 levels (500, 700-800 and 1200 µatm CO2), two light levels (100 and 70% of surface irradiance) and two nutrient levels of N, P, and K (enriched vs non-enriched treatments) in the non-calcified macroalga Cystoseira compressa (Phaeophyceae, Fucales) and calcified Padina pavonica (Phaeophyceae, Dictyotales). A suite of biochemical assays and in vivo chlorophyll a fluorescence parameters showed that elevated CO2 levels benefitted both of these algae, although their responses varied depending on light and nutrient availability. In C. compressa, elevated CO2 treatments resulted in higher carbon content and antioxidant activity in shaded conditions both with and without nutrient enrichment - they had more Chla, phenolic and fucoxanthin with nutrient enrichment and higher quantum yield (Fv/Fm) and photosynthetic efficiency (αETR) without nutrient enrichment. In P. pavonica, elevated CO2 treatments had higher carbon content, Fv/Fm, αETR, and Chla regardless of nutrient levels - they had higher concentrations of phenolic compounds in nutrient enriched, fully-lit conditions and more antioxidants in shaded, nutrient enriched conditions. Nitrogen content increased significantly in fertilised treatments, confirming that these algae were nutrient